2019
DOI: 10.1038/s41598-019-47877-z
|View full text |Cite
|
Sign up to set email alerts
|

A promising form-stable phase change material prepared using cost effective pinecone biochar as the matrix of palmitic acid for thermal energy storage

Abstract: A promising new form-stable phase change material (PA/PB) was fabricated using pinecone biochar (PB) as the supporting material of palmitic acid (PA). The biochar of PB with large surface area was produced by forest residue of pinecone, and it was cheap, environment friendly and easy to prepare. The PB was firstly utilized as the supporter of PA and the characterizations of PA/PB were analyzed by the BET, SEM, XRD, DSC, TGA, FT-IR and thermal conductivity tester. The results demonstrated that the PA was physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 51 publications
0
26
0
2
Order By: Relevance
“…The absorptions at 1472 and 1703 cm −1 were assigned to C–C vibrations and C═O stretching vibrations. Besides, 1296, 945, and 730 cm −1 were attributed to the bending vibration of in‐plane and out‐of‐plane, and in‐plane winging vibration of –OH in PA . Moreover, all of the characteristic absorption peaks from PA and diatomite were also displayed in the spectra of CPCMs.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The absorptions at 1472 and 1703 cm −1 were assigned to C–C vibrations and C═O stretching vibrations. Besides, 1296, 945, and 730 cm −1 were attributed to the bending vibration of in‐plane and out‐of‐plane, and in‐plane winging vibration of –OH in PA . Moreover, all of the characteristic absorption peaks from PA and diatomite were also displayed in the spectra of CPCMs.…”
Section: Resultsmentioning
confidence: 94%
“…The absorptions at 1472 and 1703 cm −1 were assigned to C-C vibrations and C═O stretching vibrations. Besides, 1296, 945, and 730 cm −1 were attributed to the bending vibration of in-plane and out-of-plane, and in-plane winging vibration of -OH in PA. 45,46 Moreover, all of the characteristic absorption peaks from PA and diatomite were also displayed in the spectra of CPCMs. Meanwhile, by comparing the absorption curves of PA and diatomite, no obvious peak shifts were observed in the absorption peaks of the CPCM1-CPCM7, which indicated that no chemical interaction existed and there was good compatibility between PA and diatomite.…”
Section: Ft-ir Analysismentioning
confidence: 94%
“…For the above ratio, no PCM leakage was observed after the melting temperature. The results showed that the thermal conductivity of the same ratio shape-stable PCM increased by 44% compared to the pure PCM [80].…”
Section: Shape-stable Ppcmsmentioning
confidence: 99%
“…To overcome the leakage problem of organic PCMs, some porous materials, such as mesoporous silica, diatomite, and porous carbon, were applied to support the synthesis of ss-PCMs from organic PCMs [20][21][22] . Chen et al 20 prepared wrinkled mesoporous silica (WMSN) and embedded myristic acid (MA) into WMSN to synthesize ss-PCMs, named MA/WMSN, which prevented the leakage problem of MA in the phase change process.…”
mentioning
confidence: 99%
“…Chen et al 20 prepared wrinkled mesoporous silica (WMSN) and embedded myristic acid (MA) into WMSN to synthesize ss-PCMs, named MA/WMSN, which prevented the leakage problem of MA in the phase change process. Wan et al 22 synthesized ss-PCM using pinecone biochar (PB) as the matrix and palmitic acid (PA) as the organic PCM, which not only solved the leakage problem of PA but also improved the thermal conductivity of the PCMs. Apart from the leakage problem, organic PCMs have the disadvantage of low thermal conductivity.…”
mentioning
confidence: 99%